PENGOLAHAN DEKSTRIN SAGU (METROXYLON RUMPHII) SECARA ENZIMATIS - R Sudradjat; Erra Yusnita (Jurnal Penelitian Hasil Hutan, 2002)
Sago tree (Metroxylon rumphii) is a potential source of starch and an important contributor of non timber forest products for foodstuff reserve because it has a high carbohydrate content particularly starch. The idea of converting sago starch into dextrin compound is to enhance wider use and increase the economic value of the this commodity. Dextrin has been known for its use as additives in textile industries, pulp/paper industries and pharmaceutical industries.A laboratory trial has been conducted to convert sago into dextrin harnessing the activities of particular enzymes. The aim of this trial was to figure out optimum condition of enzymatic 'sago-processing into satisfactory-quality dextrin, able to comply with the requirement of Indonesian National Standard (INS). The target is to obtain appropriate technology development in sago-derived dextrin.The result revealed that the optimum condition was obtained at substrate concentration of 25 percent with enzyme dosage at 0,9 gram per kg of substrate (dry-weight). In this condition, the dextrin solubility complies with the INS requirement; i.e 25 percent with enzyme dosage at 0,5 gram per kg of substrate (dry- weight).